Agustí Bartra: translate into the terrible Catalan solitude - Bacardí, Montserrat (Revista de Filología Románica, 2016)
Like many intellectuals committed to the Republic, Agustí Bartra (Barcelona, 1908 - Terrassa, 1982) had to embark on the road of exile in January 1939. He passed through France, the Dominican Republic and Cuba, until he arrived in Mexico in 1941. He had learned French and studied English in a selftaught way. The translation became the most suitable and affordable occupation for an intellectual who tried to make a living with writing. From then on he translated in abundance works of poetry and narrative, vocationally and professionally, for the leading Mexican publishers. Catalan translated Una antologia de la lírica nord-americana (1951) and some other work that has remained unpublished. Returning to the country in 1970, he continued to translate into Catalan and Spanish, under conditions not too different from those of the previous era. The binomial exile and translation obstinately persisted.